1989
DOI: 10.1164/ajrccm/139.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Airway Responsiveness to Methacholine Does Not Change during Chemotherapy in Patients with Chronic Bronchitis and Bronchial Carcinoma

Abstract: To investigate the role of leukocytes and neutrophils in the peripheral blood on airway responsiveness, we studied nine patients with chronic bronchitis and histologically proved bronchial carcinoma before and after chemotherapy. The concentration of methacholine (in mg/ml) necessary to increase specific airway resistance by 100%, PC100SRaw, and the number of leukocytes and neutrophils (in cells x 10(6)/ml) were measured before, and 8 and 16 days after chemotherapy. Mean (SEM) total number of leukocytes decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…These data have suggested that airway responsiveness cannot always be explained by airway inflammation. This hypothesis is further supported by our finding that in patients with chronic bronchitis and bronchial carcinoma, chemotherapy-induced leucocyte deple tion does not influence airway responsive ness to methacholine [47], In patients with cystic fibrosis, airway hyperresponsive ness is less pronounced than in asthmatics [39], though the airways of patients with cystic fibrosis did show signs of inflamma tion.…”
Section: Smoking Chronic Bronchitis and Cystic Fibrosissupporting
confidence: 59%
“…These data have suggested that airway responsiveness cannot always be explained by airway inflammation. This hypothesis is further supported by our finding that in patients with chronic bronchitis and bronchial carcinoma, chemotherapy-induced leucocyte deple tion does not influence airway responsive ness to methacholine [47], In patients with cystic fibrosis, airway hyperresponsive ness is less pronounced than in asthmatics [39], though the airways of patients with cystic fibrosis did show signs of inflamma tion.…”
Section: Smoking Chronic Bronchitis and Cystic Fibrosissupporting
confidence: 59%
“…BHR is condition in which airways show a much bigger bronchoconstrictive response to various provocative specific and non-specific agents than it is normal ( 1 ). Bronchial inflammation is the fundamental of BHR ( 1 , 2 ). The more expressive inflammation of bronchial mucosa, the more expressive BHR is ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial inflammation is the fundamental of BHR ( 1 , 2 ). The more expressive inflammation of bronchial mucosa, the more expressive BHR is ( 2 ). If the level of BHR is bigger there is bigger number of exacerbations of disease ( 1 , 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations